BAZNAS Strategy to Increase the Participation of Persons With Disabilities in the Labor Market - Prabowo, Dicky irawan; Dwi Retno (Islamic Economics and finance in Focus, 2026)
This study aims to explore how BAZNAS implements zakat programs based on the SDGs framework, particularly in achieving SDG target number 8, which focuses on inclusive economic growth and creating an inclusive work environment for individuals with disabilities. This study uses a qualitative method with a case study approach, supported by quantitative data analysis. Data were collected through interviews and a review of relevant literature. This study examines the role of BAZNAS in supporting economic empowerment through productive zakat programs, and how these programs contribute to achieving sustainable and inclusive economic growth targets in line with the SDGs agenda. In this context, the research explores the challenges faced in program implementation, including institutional, cultural, and technical constraints. In addition, this study also examines the impact of zakat on the empowerment of vulnerable communities, including persons with disabilities, with a focus on efforts to create job opportunities and supportive environments. The research results show that BAZNAS plays a significant role in supporting inclusive economic growth through productive zakat schemes. However, there are several challenges regarding program sustainability and community participation. The implications of this research are expected to provide insights for stakeholders in formulating more inclusive policies to support the achievement of the SDGs, especially in the sectors of disability and economic empowerment.